FORMATION OF STUDENTS' READINESS FOR CREATIVITY PROFESSIONAL ACTIVITY (Pedagogy of Higher and Secondary Education, 2008)
The article deals with various problems of forming of readiness for іn ative pedagogical activities, and making optimum conditions of pedagogical process